2021
DOI: 10.1007/s11356-021-16536-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PM1 exposure on total and cause-specific respiratory diseases: a systematic review and meta-analysis

Abstract: An increasing number of studies examined the potential effects of PM1 (submicronic particulate matter with an aerodynamic diameter ≤ 1 μm) on the risk of respiratory diseases; however, the results have been inconclusive. This study aimed to determine the overall association between PM1 with total and cause-specific respiratory diseases. A systematic review and meta-analysis was conducted with 68 related articles retrieved, and six articles met the full inclusion criteria for the final analysis. For a 10 μg/m3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Beijing (Wang et al 2021a). However, a meta-analysis of hospitalisation, EDV and prevalence data from China, Vietnam and America published between 2004 and 2021 showed that PM1 exposure had no significant association with increase in RI hospitalisation risks (Hu et al 2022). Therefore, there is still a lack of understanding regarding how PM1 exposure contributes to the development of respiratory diseases and how long it takes for disease progression, which may also explain the inconsistency of results reported here.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Beijing (Wang et al 2021a). However, a meta-analysis of hospitalisation, EDV and prevalence data from China, Vietnam and America published between 2004 and 2021 showed that PM1 exposure had no significant association with increase in RI hospitalisation risks (Hu et al 2022). Therefore, there is still a lack of understanding regarding how PM1 exposure contributes to the development of respiratory diseases and how long it takes for disease progression, which may also explain the inconsistency of results reported here.…”
Section: Discussionmentioning
confidence: 60%
“…It was found that PM1 accounts for 80% of PM2.5 mass contents (Chen et al 2018), indicating that PM2.5-related health effects is likely dependent on the existence of PM1.In fact, short-term PM1-dependent effects have been previously implicated in the cause of various diseases by assessing relative health risk metrics. This includes emergency ambulance call, emergency department visits (EDV), and mortality (GB Chen et al 2017a;Hu et al 2022;H Lin et al 2018;LJ Liu et al 2021;Wang et al 2021a;Yin et al 2019;Zhang et al 2020b). Recently, studies have mostly focused on the implications of short-term PM1 exposure in hospital admissions related to cardiovascular diseases and strokes (Liu et al 2022;Tian et al 2023;Zheng et al 2023;Zhou et al 2023), less is understood on the impact on respiratory disease hospitalisations (Li et al 2023;Zhang et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we focused on a limited list of 45 contaminants commonly found in dwellings, selected based on their known harmful effects and availability of data. However, an important limitation is the omission of emerging contaminants like PM 1 and ultrafine particles PM 0.1 , fungicides and pesticides, flame retardants, and endocrine disruptors such as phthalates, which have gained increasing attention in research. , These substances have the potential to significantly contribute to harm in indoor environments. Therefore, future studies should expand the scope to include these emerging contaminants, enabling a more comprehensive assessment of harm.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hu et al (2022) conducted a systematic review finding that, for a 10 µg m −3 increase in PM 1 , there is a pooled odds ratio of 1.05 (95% CI 0.98-1.12) for total respiratory diseases, 1.25 (95% CI 1.00-1.56) for asthma, and 1.07 (95% CI 1.04-1.10) for pneumonia. This establishes that there is a positive association between this contaminant and these health outcomes.…”
Section: Pm I -24 H Data Anddescriptive Statisticsmentioning
confidence: 99%